1985
DOI: 10.1080/09553008514550771
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Relationship between the Radiation Resistance and Glutathione Content of Human and Rodent Cells after Treatment with Dexamethasonein Vitro

Abstract: A 20 h pre-treatment of human cells from normal (foetal lung) or malignant origin (glioma, lines U118 MG and U251 MG and bladder carcinoma, line EJ) with dexamethasone failed to increase their radiation resistance in vitro despite a 2-fold increase in the GSH content of a glioma cell line, U251 MG, and a small but significant increase in the GSH content of EJ bladder carcinoma cells. In contrast, there was a correlation between an increase in radiation resistance and an elevated GSH content of rodent cells (Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…48 Similarly, GCs stimulated p21 gene expression by targeting multiple transcriptional elements within a steroid responsive region of the p21 WAF1/CIP1 promoter in rat hepatoma cells. 49 Another possibility, not examined in this study, is that DEX may have upregulated some drug-detoxifying factors such as found for metallothionein, [50][51][52] O6-methylguanine-DNA methyltransferase (MGMT), 53-55 P-glycoprotein 56,57 or glutathione, 58 which may have influenced the effectiveness of chemotherapy. 59…”
Section: Effect Of Gcs On Cell Proliferation and Cell Cycle Progressionmentioning
confidence: 99%
“…48 Similarly, GCs stimulated p21 gene expression by targeting multiple transcriptional elements within a steroid responsive region of the p21 WAF1/CIP1 promoter in rat hepatoma cells. 49 Another possibility, not examined in this study, is that DEX may have upregulated some drug-detoxifying factors such as found for metallothionein, [50][51][52] O6-methylguanine-DNA methyltransferase (MGMT), 53-55 P-glycoprotein 56,57 or glutathione, 58 which may have influenced the effectiveness of chemotherapy. 59…”
Section: Effect Of Gcs On Cell Proliferation and Cell Cycle Progressionmentioning
confidence: 99%
“…However, dexamethasone-induced radioresistance does not occur in all human cell types. Dexamethasone did not confer radioresistance in breast carcinoma cell line MCF-7 nor in normal diploid fibroblast strain AG 1522 [2], nor in glioblastoma cell lines Ul18 MG and U251 MG [15].…”
Section: Resultsmentioning
confidence: 88%
“…Nederman et al [9] reported that there was a slight tendency towards radio-protection of human glioma cells during continuous exposure to betamethasone. Millar et al [10] reported that no changes in radiosensitivity could be seen when the same type of human glioma cells were treated with 1/~g/ml of dexamethasone. To sort out this discrepancy we decided to carry out a more extensive study using a continuous exposure of betamethasone.…”
Section: Introductionmentioning
confidence: 99%
“…To sort out this discrepancy we decided to carry out a more extensive study using a continuous exposure of betamethasone. The study by Nederman et al [9] on the effects of betamethasone was very limited while the study by Millar et al [10] on dexamethasone was carried out in more detail. Cultured glioma cells are known to have a low cloning efficiency [10,11] and it is therefore difficult to clone them according to the original description by Puck and Marcus [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation